Understanding Capacitance Variation in Sub-nanometer Pores by in Situ Tuning of Interlayer Constrictions - Galhena, Dona T. L; Bayer, Bernhard C; Hofmann, Stephan; Amaratunga, Gehan A. J (ACS nano, 2016)
The contribution of subnanometer pores in carbon electrodes to the charge-storage mechanism in supercapacitors has been the subject of intense debate for over a decade. Here, we provide a model system based on graphene oxide, which employs interlayer constrictions as a model for pore sizes that can be both controllably tuned and studied in situ during supercapacitor device use. Correlating electrochemical performance and in situ tuning of interlayer constrictions, we observe a peak in specific capacitance when interlayer constriction size reaches the diameters of unsolvated ions, supporting the hypothesized link between loss of ion solvation shell and anomalous capacitance increase for subnanometer pores.